Legal framework of alternative dispute resolution in tribunal for consumer claims in Malaysia / Su’aida Safei - Safei, Su’aida (2022)
The Tribunal for Consumer Claims (TCC) was established to provide an easier and a speedier mechanism for consumers to seek redress against the traders outside the court. The President of the TCC is allowed in section 107 of the Consumer Protection Act 1999 (CPA) to assist parties in negotiating their settlement. However, the non specification of the settlement method led to the wide discretion of the President. The imbalance capability of disputing parties due to non-legal representation, enforcement of awards and difficulties faced by the President in deciding technical issues are also unsettled issues. This thesis, firstly, aims to identify the relevant provisions governing the TCC, which contain elements of alternative dispute resolution (ADR) in the CPA and the Consumer Protection (the Tribunal for Consumer Claims) Regulations 1999 (TCC Regulations) in enhancing its role as an alternative method to litigation in court. In acknowledging the different behaviours (such as the weak, the confused and the vulnerable consumers) of consumers and with the aim of empowering consumers, the thesis analyses the legal position in the operation of TCC at different stages, namely, the pre-hearing stage, the “hearing” stage and the post-hearing stage. Content analysis on the relevant statutes, observations and interviews are adopted in this thesis. A comparative study is also made on the practice of court mediation in the Malaysian courts, the practices of Tribunals in the area of consumer disputes in Australia (the Civil and Administrative Tribunal in Queensland and the Civil and Administrative Tribunal in New South Wales), the Disputes Tribunal in New Zealand, the Small Claims Tribunal in Singapore, the practice of lay judges in France and Germany and the practice of having lay participation in the decision making at the Industrial Court and at the Disciplinary Board of the legal profession in Malaysia for lessons to be learned. By adopting the qualitative method and the doctrinal legal research method, it is suggested that a suitable framework for ADR at the TCC includes to identify the specific ADR, to add the different categories of members of TCC, to include the lay participation in the composition of members at TCC, to enhance the use of technology in the hearing, to add the representatives of parties, to allow legal representation in certain circumstances, to introduce the internal appeal and to improve the enforcement of award. It is hoped that the suggested framework will lead to a better implementation of ADR at TCC, and consequently, improve the TCC’s function as a better dispute resolution mechanism for consumers, and at the same time empowering the consumers.